The neuroprotective effect of Sulindac after ischemia-reperfusion injury in rats - Cosar,Murat (2014)
PURPOSE: To investigate the neuroprotective effects of Sulindac on the hippocampal complex after global cerebral ischemia/reperfusion (I/R) injury in rats.METHODS: Thirty one Sprague-Dawley rats were used, distributed into group I (sham) n:7 were used as control. For group II (n:8), III (n:8) and IV (n:8) rats, cerebral ischemia was performed via the occlusion of bilateral internal carotid artery for 45 minutes and continued with reperfusion process. 0.3 mL/kg/h 0.9 % sodium chloride was infused intraperitoneally to the Group II rats before ischemia, 5μg/kg/h/0.3 ml sulindac was infused intraperitoneally to the Group III rats before ischemia and 5μg/kg/h/0.3 ml sulindac was infused intraperitoneally to the Group IV rats after ischemia and before reperfusion process. The levels of MDA, GSH and MPO activity were measured in the left hippocampus tissue. The hippocampal tissue of all group members were taken for histopathological study.RESULTS: The MDA and MPO levels increased from group I (control) to group II (I/R) (P<0.05) and decreased from group II (I/R) to group III (presulindac + I/R) and IV (postsulindac + I/R) (P<0.05). Beside these, the GSH levels decreased from group I (control) to group II (I/R) (P<0.05) and increased from group II (I/R) to group III (presulindac + I/R) and IV (postsulindac + I/R) (P<0.05).The number of apoptotic neurons increased from group I (control) to group II (I/R) (P<0.05) and decreased from group II (I/R) to group III (presulindac + I/R) and IV (postsulindac + I/R) (P<0.05).CONCLUSION: The Sulindac may have neuroprotective effects on ischemic neural tissue to prevent the reperfusion injury after ischemia.